Microglial autophagy defect causes parkinson disease-like symptoms by accelerating inflammasome activation in mice. Issue 12 (1st December 2020) - Cheng, Jinbo; Liao, Yajin; Dong, Yuan; Hu, Han; Yang, Nannan; Kong, Xiangxi; Li, Shuoshuo; Li, Xiaoheng; Guo, Jifeng; Qin, Lixia; Yu, Jiezhong; Ma, Cungen; et al.
ABSTRACT: Microglial activation-induced neuroinflammation is closely associated with the development of Parkinson disease (PD). Macroautophagy/autophagy regulates many biological processes, but the role of autophagy in microglial activation during PD development remains largely unclear. In this study, we showed that deletion of microglial Atg5 caused PD-like symptoms in mice, characterized by impairment in motor coordination and cognitive learning, loss of tyrosine hydroxylase (TH) neurons, enhancement of neuroinflammation and reduction in dopamine levels in the striatum. Mechanistically, we found that inhibition of autophagy led to NLRP3 (NLR family pyrin domain containing 3) inflammasome activation via PDE10A (phosphodiesterase 10A)–cyclic adenosine monophosphate (cAMP) signaling in microglia, and the sequential upregulation of downstream IL1B/IL-1β in turn increased the expression of MIF (macrophage migration inhibitory factor [glycosylation-inhibiting factor]), a pro-inflammatory cytokine. Inhibition of NLRP3 inflammasome activation by administration of MCC950, a specific inhibitor for NLRP3, decreased MIF expression and neuroinflammatory levels, and rescued the loss of TH neurons in the substantial nigra (SN). Interestingly, we found that serum MIF levels in PD patients were significantly elevated. Taken together, our results reveal an important role of autophagy in microglial activation-driven PD-like symptoms, thus providing potential targets for the clinical treatment of PD. Abbreviations : ATG: autophagy related; cAMP: cyclic adenosine monophosphate; cKO: conditional knockout; NOS2/INOS: nitric oxide synthase 2, inducible; IL1B: interleukin 1 beta; ITGAM/CD-11b: integrin alpha M/cluster of differentiation molecule 11B; MAP1LC3: microtubule-associated protein 1 light chain 3; MIF: macrophage migration inhibitory factor (glycosylation-inhibiting factor); NLRP3: NLR family pyrin domain containing 3; PBS: phosphate-buffered saline; PD: parkinson disease; PDE10A: phosphodiesterase 10A; SN: substantial nigra; TH: tyrosine hydroxylase; TNF: tumor necrosis factor; WT: wild type.